2021
DOI: 10.3390/jcp1040034
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Countermeasure Readability on Security Intentions

Abstract: Human failure is a primary contributor to successful cyber attacks. For any cybersecurity initiative, it is therefore vital to motivate individuals to implement secure behavior. Research using protection motivation theory (PMT) has given insights into what motivates people to safeguard themselves in cyberspace. Recent PMT results have highlighted the central role of the coping appraisal in the cybersecurity context. In cybersecurity, we cope with threats using countermeasures. Research has shown that counterme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Various models and metrics offer a quantitative approach to measuring the implications of cybersecurity in smart grids [203] • User Awareness and Training Metrics: these measure the effectiveness of cybersecurity education programs through completion rates, campaign frequency, and policy adherence.…”
Section: Quantitative Models and Metrics For Assessing The Implicatio...mentioning
confidence: 99%
“…Various models and metrics offer a quantitative approach to measuring the implications of cybersecurity in smart grids [203] • User Awareness and Training Metrics: these measure the effectiveness of cybersecurity education programs through completion rates, campaign frequency, and policy adherence.…”
Section: Quantitative Models and Metrics For Assessing The Implicatio...mentioning
confidence: 99%
“…For example, word prevalence, entropy, perplexity, word count, particular character count, word probability, morpheme count, word frequencies, named entity recognition, sentence analysing features and many more. Some tooling uses more than 200 features [12], or even more than 400 formulas [5].…”
Section: Readability Toolingmentioning
confidence: 99%
“…Second, this study demonstrated that the majority of prior studies (84%) focused on two goals: information security policy compliance and management information security. It shows that researchers are less prone to focus on other topics, such as the effectiveness of information security communication (Smit et al, 2021), SME awareness-raising, and SMEs' risk perception. However, these topics are important, and studies show that information security communication and risk perception impact CEOs' decision-making, motivation to comply, and effective protection (Renaud and Weir, 2016 [P6]; Barlette and Jaouen, 2019 [P16]).…”
Section: Discussionmentioning
confidence: 99%